Identification of Megatrends Affecting Complexity in Logistics Systems - Wolfgang Kersten; Birgit von See; Henning Skirde (Next Generation Supply Chains: Trends and Opportunities. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
To cope with megatrends companies often react with changes resulting in complexity. Thus, managing complexity results in increasing costs. Especially logistics service providers have to cope with cost pressure and are due to their size often limited in case of resources. In order to assess these costs an adequate complexity cost assessment has to be developed. Before developing such an approach, the question what drives complexity in logistics systems has to be raised and answered. In this paper, 16 megatrends affecting logistics systems are identified through literature review, expert interviews, and a focus group discussion. The identification and discussion of these megatrends with regard to complexity provides a first step towards a complexity cost assessment. Megatrends can thereby function as important drivers of complexity in logistics systems.
10419/209187; https://econpapers.repec.org/RePEc:zbw:hiclpr:18
Keywords: 650; megatrends; complexity; logistics systems; literature review